EXPLORING CREATIVE THINKING SKILL - Wulandari, Hilaria Yesieka Ayu; Ekawati, Rooselyna; Shodikin, Ali (Jurnal Pendidikan Matematika (JUPITEK), 2024)
This study aims to describe students' abilities with visual-spatial and logical-mathematical intelligence in solving contextual mathematical problems. This qualitative research involved two eighth-grade students from a junior high school, each with a background in logical-mathematical and visual-spatial intelligence. The task consisted of two questions that asked students to create two park designs and two alternative payment methods for the "Suroboyo Bus." These findings show both subjects’ complete fluency and flexibility indicators in creative thinking. Subjects exhibit the ability to generate diverse solution pathways and apply various problem-solving strategies. Furthermore, the creative thinking skills displayed by the subject contribute to their comprehensive understanding of mathematical concepts and foster deeper engagement with the subject. The analysis results show that students with logical-mathematical intelligence were able to solve the problems well and came up with various alternative answers that other students did not consider. Students with visual-spatial intelligence were able to solve the problems successfully but did not find ideas to search for alternative answers beyond what was already presented. These findings indicate that both students with visual-spatial and logical-mathematical intelligence were capable of solving the given contextual problems, although there is still room for improvement